Design of a virtual reality framework for maintainability and assemblability test of complex systems - Marzano, Adelaide; Friel, Imelda; Erkoyuncu, John Ahmet; Court, Samuel (Elsevier, 2015)
This paper presents a unique environment whose features are able to satisfy requirements for both virtual maintenance and virtual manufacturing through the conception of original virtual reality (VR) architecture. Virtual Reality for the Maintainability and Assemblability Tests (VR_MATE) encompasses VR hardware and software and a simulation manager which allows customisation of the architecture itself as well as interfacing with a wide range of devices employed in the simulations. Two case studies are presented to illustrate VR_MATE's unique ability to allow for both maintainability tests and assembly analysis of an aircraft carriage and a railway coach cooling system respectively. The key impact of this research is the demonstration of the potentialities of using VR techniques in industry and its multiple applications despite the subjective character within the simulation. VR_MATE has been presented as a framework to support the strategic and operative objectives of companies to reduce product development time and costs whilst maintaining product quality for applications which would be too expensive to simulate and evaluate in the real world.
Keywords: Virtual Reality; Assemblability; Manufacturing Systems